Paulus – en jødisk integrationstænker og -praktiker - Larsen, Kasper Bro (Dansk Teologisk Tidsskrift, 2025)
This article, “The Apostle Paul: A Jewish Integrationist Thinker and Practitioner,” examines Paul’s acculturation strategy of integration (“togetherness in diversity”) in comparison with competing strategies within the early Christ movement, for example the assimilation model (“togetherness in similarity”) represented by Paul’s various opponents in Galatians and Romans, and the segregation model (“separateness in diversity”) endorsed by the Apostolic Council. Contrary to prevailing views in contemporary scholarship, the study argues that some of Paul’s Christ groups, including the Corinthian one, were interethnic, consisting of both Gentile and Jewish members. Paul regarded this diversity as a foreshadowing of the imminent, eschatological events: the Messiah’s return to unite Jews and Gentiles before the God of Israel. This gospel of interethnic integration emerges consistently throughout Paul’s letters. However, the ultimate success of his Gentile mission contributed to a growing Gentile-dominated trajectory within the Christ movement, which led it in a more segregationist direction over time.